Additional TCRV beta primers and minor method modifications improve detection of clonal T-cell populations by RT-PCR. Issue 1 (February 1997) - Lynas, C; Howe, D
Abstract : The TCRV beta RT-PCR method for detection of clonal populations of T cells which we described previously could not detect clones that used certain variable (V) beta region families. V beta 2, 4, 8.3, and 18 had insufficient homology with the original consensus V region primer. Two new primers have been designed which work well and are able to amplify from V beta families previously undetectable by this RT-PCR. In addition, minor alterations to the cDNA synthesis and gel analysis of the PCR products make the results even easier to interpret. All the Diversity/Joining (D/J) region primer combinations except for D2/J2 have been omitted, and terminating the reverse transcription by heating prior to PCR greatly improves amplification with these primers. Use of 8% and/or 10% polyacrylamide gels increases clarity. Inclusion of the modifications described will reduce false reporting of patients as having a polyclonal T-cell population.